যদি \(bcx=cay=abz\) হয়, তবে প্রমান কর যে, \(\cfrac{ax+by}{a^2+b^2}=\cfrac{by+cz}{b^2+c^2}=\cfrac{cz+ax}{c^2+a^2}\) Madhyamik 2016 , 2004


ধরি, \(bcx=cay=abz=k\) [\(k\ne0\)]
\(\therefore x=\cfrac{k}{bc}, y=\cfrac{k}{ca}\) এবং \(z=\cfrac{k}{ab}\)

প্রথম রাশি \(=\cfrac{ax+by}{a^2+b^2}\)
\(=\cfrac{a.\cfrac{k}{bc}+b.\cfrac{k}{ca}}{a^2+b^2}\)
\(=\cfrac{\cfrac{ak}{bc}+\cfrac{bk}{ca}}{a^2+b^2}\)
\(=\cfrac{\cfrac{a^2k+b^2k}{abc}}{a^2+b^2}\)
\(=\cfrac{k(a^2+b^2)}{abc(a^2+b^2)}\)
\(=\cfrac{k}{abc}\)

দ্বিতীয় রাশি \(=\cfrac{by+cz}{b^2+c^2}\)
\(=\cfrac{b.\cfrac{k}{ca}+c.\cfrac{k}{ab}}{b^2+c^2}\)
\(=\cfrac{\cfrac{bk}{ca}+\cfrac{ck}{ab}}{b^2+c^2}\)
\(=\cfrac{\cfrac{b^2k+c^2k}{abc}}{b^2+c^2}\)
\(=\cfrac{k(b^2+c^2)}{abc(b^2+c^2)}\)
\(=\cfrac{k}{abc}\)

তৃতীয় রাশি \(=\cfrac{cz+ax}{c^2+a^2}\)
\(=\cfrac{c.\cfrac{k}{ab}+a.\cfrac{k}{bc}}{c^2+a^2}\)
\(=\cfrac{\cfrac{ck}{ab}+\cfrac{ak}{bc}}{c^2+a^2}\)
\(=\cfrac{\cfrac{c^2k+a^2k}{abc}}{c^2+a^2}\)
\(=\cfrac{k(c^2+a^2)}{abc(c^2+a^2)}\)
\(=\cfrac{k}{abc}\)

\(\therefore \cfrac{ax+by}{a^2+b^2}=\cfrac{by+cz}{b^2+c^2}=\cfrac{cz+ax}{c^2+a^2}\) (প্রমাণিত)

Similar Questions